Wolfram Paulus - Arnold, Andrey (Filmarchiv Austria, 2022)
His critically acclaimed debut feature, Hideouts (1986), established screenwriter and director Wolfram Paulus (1957-2020) as an important voice of New Austrian Film. Paulus devoted his career to chronicling his homeland and its inhabitants. Over the course of the 1990s, he transitioned from stylistically ambitious character studies for cinema to TV films with broad public appeal. Drama and comedy were his preferred genres. He also directed children's films and dwelled on historical topics, mostly from the National Socialist period. Beyond the well-known fictional features, Paulus created experimental and documentary works. Moreover, he was a committed pedagogue and produced many educational films with pupils. This edited collection offers interdisciplinary perspectives on Paulus' multifaceted oeuvre, which has previously received little scholarly attention. The chapters examine production and reception, motifs and aesthetic strategies, film education and unmade projects. This is complemented by a detailed filmography and interviews with Wolfram Paulus and his colleagues.